Survey of Foreign Language Course Registrations and Student Contact Hours in Final Report - Brod, Richard I.; Modern Language Association of America, New York, NY. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
This report is based on a questionnaire survey sent to the registrars of all two-year and four-year colleges and universities in the United States. Replies were received from 2,494 institutions, of which 2,313 reported registrations in one or more foreign languages. The fall 1974 survey shows a decline of 6.2% in total foreign language registrations between 1972, the year of the last previous survey conducted by the MLA, and 1974. Registrations declined by more than ten percent in French, German, and Russian, but by less than one percent in Italian and Spanish. There were increases for Latin, Ancient Greek, and a number of the so-called "other" or less commonly taught languages. Spanish continues to be the leading language in U.S. colleges, accounting for over 38% of the total. The report consists of an introduction, five summary tables, thirteen detailed tables, and an institutional directory. The detailed tables present data by state or by region for the seven most commonly taught languages and for the aggregate of "other" languages, as well as detailed comparative figures from surveys undertaken in 1965, 1970, and 1972. (Author)
Sponsoring Agency: Bureau of Postsecondary Education (DHEW/OE), Washington, DC. Div. of International Education.
Contract Number: OEC-0-74-2125.
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Declining Enrollment; Enrollment; Enrollment Influences; Enrollment Rate; Enrollment Trends; French; German; Greek; Higher Education; Italian; Language Enrollment; Language Instruction; Latin; Questionnaires; Russian; Second Language Learning; Spanish; Statistical Surveys; Surveys; Uncommonly Taught Languages; Reports, Research